1996
DOI: 10.1037/0012-1649.32.4.604
|View full text |Cite
|
Sign up to set email alerts
|

The effect of common rearing on adolescent adjustment: Evidence from a U.S. adoption cohort.

Abstract: We thank Thomas i. Bouchard, Robert Cudeck, and Auke Tellegen for their helpful comments on an earlier version of the article. The research presented was supported in part by Grants R01-MH42620 and K02-AAO0175 from the National Institutes of Health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 31 publications
6
56
1
Order By: Relevance
“…The shared environmental estimates did not reach significance, however. Our findings converge with those from studies of both adopted children (McGue, Sharma, & Benson, 1996;Neiderhiser & McGuire, 1994) and other types of siblings (McGuire et al, 1999). Multiple studies using different samples and methodology have also found that shared environmental influences have little to no impact on self-esteem level.…”
Section: Behavioral Genetics Analysessupporting
confidence: 33%
“…The shared environmental estimates did not reach significance, however. Our findings converge with those from studies of both adopted children (McGue, Sharma, & Benson, 1996;Neiderhiser & McGuire, 1994) and other types of siblings (McGuire et al, 1999). Multiple studies using different samples and methodology have also found that shared environmental influences have little to no impact on self-esteem level.…”
Section: Behavioral Genetics Analysessupporting
confidence: 33%
“…The lack of any evidence for a relationship between parental alcoholism and drinking among ALDH deficient individuals is consistent with other research suggesting that parent-offspring resemblance for drinking behavior is primarily genetically and not environmentally mediated (Cloninger, Bohman, & Sigvardsson, 1981;Goodwin, Schulsinger, Hermansen, Guze, & Winokur, 1973;McGue, Sharma, & Benson, 1996a). Our finding that sibling drinking behavior was consistently and moderately associated with adolescent drinking behavior implicates siblings as a potent but arguably underappreciated source of familial environmental effect on adolescent behavior (McGue, Sharma, & Benson, 1996b;Slomkowski, Rende, Conger, Simons, & Conger, 2001;Slomkowski, Rende, Novak, Lloyd-Richardson, & Niaura, 2005).…”
Section: Aldh Deficiency and Models Of Gene-environment Interplaysupporting
confidence: 79%
“…The correlations between parenting and teacherrated aggression were insignificant in adoptive families. The correlations between adolescent problems and ratings of the quality of family relationships by their mothers were higher in families in which parents reared their own children than in adoptive families (McGue, Sharma, & Benson, 1996). Taken together, these finding suggest that genotypic differences among parents influence their parenting and that these genotypic differences are transmitted to children, in whom they are manifested by psychiatric symptoms.…”
Section: Dz Twinssupporting
confidence: 51%